Altered proteolytic activities of ADAMTS-4 expressed by C-terminal processing. - Kashiwagi, M; Enghild, J; Gendron, C; Hughes, C; Caterson, B; Itoh, Y; Nagase, H (2004)
ADAMTS-4 (a disintegrin and metalloprotease with thrombospondin motifs) is a multidomain metalloproteinase belonging to the reprolysin family. The enzyme cleaves aggrecan core protein at several sites. Here we report that the non-catalytic ancillary domains of the enzyme play a major role in regulating aggrecanase activity, with the C-terminal spacer domain masking the general proteolytic activity. Expressing a series of domain deletion mutants in mammalian cells and examining their aggrecan-degrading and general proteolytic activities, we found that full-length ADAMTS-4 of 70 kDa was the most effective aggrecanase, but it exhibited little activity against the Glu(373)-Ala(374) bond, the site originally characterized as a signature of aggrecanase activity. Little activity was detected against reduced and carboxymethylated transferrin (Cm-Tf), a general proteinase substrate. However, it readily cleaved the Glu(1480)-Gly(1481) bond in the chondroitin sulfate-rich region of aggrecan. Of the constructed mutants, the C-terminal spacer domain deletion mutant more effectively hydrolyzed both the Glu(373)-Ala(374) and Glu(1480)-Gly(1481) bonds. It also revealed new activities against Cm-Tf, fibromodulin, and decorin. Further deletion of the cysteine-rich domain reduced the aggrecanase activity by 80% but did not alter the activity against Cm-Tf or fibromodulin. Further removal of the thrombospondin type I domain drastically reduced all tested proteolytic activities, and very limited enzymatic activity was detected with the catalytic domain. Full-length ADAMTS-4 binds to pericellular and extracellular matrix, but deletion of the spacer domain releases the enzyme. ADAMTS-4 lacking the spacer domain has promiscuous substrate specificity considerably different from that previously reported for aggrecan core protein. Finding of ADAMTS-4 in the interleukin-1alpha-treated porcine articular cartilage primarily as a 46-kDa form suggests that it exhibits a broader substrate spectrum in the tissue than originally considered.